2018
DOI: 10.3390/nano8100796
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tb@Sr-MOF as Self-Calibrating Luminescent Sensor for Nutritional Antioxidant

Abstract: Sesamol, is well-known antioxidant and can reduce the rate of oxidation and prolong expiration date. It is also potentially antimutagenic and antihepatotoxic, the detection of sesamol is important and remains a huge challenge. Herein, a new 3D alkaline earth Sr metal organic framework [Sr(BDC)·DMAC·H2O]n (BDC = benzene-1,4-dicarboxylate; DMAC = N,N-dimethylacetamide) is synthesized and a probe based on Tb3+ functionalized Sr-MOF. The Tb(3+)@Sr-MOF showed good luminescence and thermal property. Due to the energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…In previous studies, the luminescent quenching mechanism based on MOFs has been shown to be caused by structural collapse, competition absorption, or interactions between the detected objects and MOF frameworks. The consistent PXRD results confirmed the intact skeleton after amino acid detection, indicating that the luminescence quenching was not caused by structural collapse (Figure S4). The non-overlapping UV–vis absorption spectra of aspartic acid and excitation spectra of Eu 3+ @ 1 exclude the competitive adsorption (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the luminescent quenching mechanism based on MOFs has been shown to be caused by structural collapse, competition absorption, or interactions between the detected objects and MOF frameworks. The consistent PXRD results confirmed the intact skeleton after amino acid detection, indicating that the luminescence quenching was not caused by structural collapse (Figure S4). The non-overlapping UV–vis absorption spectra of aspartic acid and excitation spectra of Eu 3+ @ 1 exclude the competitive adsorption (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…The LOD of FMOF for nitenpyram was 0.03 µg/mL. MOF-5 [Zn 4 O(BDC) 3 DEF (BDC = 1,4-benzenedicarboxylate, DEF = diethylformamide)] was designed by Kumar et al [ 67 ] for sensing a nitro group containing OPs including parathion, methyl parathion, paraoxon, and fenitrothion. MOF-5 exhibited strong green emission under the UV-light and, upon the addition of Ops, the fluorescence emission would be outstandingly quenched via the PET.…”
Section: Nmofs For Food Qualitymentioning
confidence: 99%
“…Terbium is an essential element of the rare earth family that presents complex optical, magnetic, and electronic properties. It is also an appropriate candidate for applications in the glass industry [ 48 , 49 ], information industry [ 50 ], polymers [ 51 , 52 ], bio-chemical sensors [ 53 , 54 , 55 ], and solar cells [ 56 , 57 , 58 ]. Terbium is unavoidably present in the environment, organisms, and food chains due to its extensive development and utilization.…”
Section: Hydroxyapatite Doped With Photoluminescent Elementsmentioning
confidence: 99%